Persistent pathology of the patent foramen ovale: a review of the literature. Issue 2 (4th July 2021) - Cho, Kenneth K; Khanna, Shaun; Lo, Phillip; Cheng, Daniel; Roy, David
Summary: A patent foramen ovale (PFO) is an interatrial shunt, with a prevalence of 20–34% in the general population. While most people do not have secondary manifestations of a PFO, some reported sequelae include ischaemic stroke, migraine, platypnoea–orthodeoxia syndrome and decompression illness. Furthermore, in some cases, PFO closure should be considered for patients before neurosurgery and for patients with concomitant carcinoid syndrome. Recent trials support PFO closure for ischaemic stroke patients with high risk PFOs and absence of other identified stroke mechanisms. While PFOs can be associated with migraine with auras, with some patients reporting symptomatic improvement after closure, the evidence from randomised controlled trials is less clear in supporting the use of PFO closure for migraine treatment. PFO closure for other indications such as platypnoea–orthodeoxia syndrome, decompression illness and paradoxical embolism are based largely on case series with good clinical outcomes. PFO closure can be performed as a day surgical intervention with high procedural success and low risk of complications.